What does pump sets electrification change? impacts on cropping patterns, productivity and incomes in West Bengal - Buisson, Marie-Charlotte (2015)
West Bengal is currently implementing new policies facilitating the access to electrified irrigation for farmers and expects to initiate a second Green Revolution. Based on primary data, this paper aims to estimate the potential impact of these electrification policies. Using a discontinuity design and propensity score methods, we identify that electrification induces a significant change in the cropping patterns and more water intensive crops, especially boro rice, are preferred by farmers. In addition, the cropping intensity is also higher for electric pump owners. However, we cannot identify any significant quantity impact, which means that the yields are not benefitting from an access to electric pumps. On the contrary, there is a significant and positive price effect for boro rice: the farmers irrigating with electrified tubewells have significantly higher value added and consequently higher incomes from their farming activities. Finally, we identify a positive impact of tubewell electrification on the number of irrigations; considered together with the absence of impact on yields, this result questions the sustainability of the electrification policies to manage the groundwater resource.